The legal framework for building on agricultural property - Sabri Said Eliathi , Fatin; Oukid, Nabil (Journal of Human Sciences, 2020)
The agricultural real estate plays an important role in achieving the food security of the state, through the provision of agricultural products that help to a great extent to achieve self-sufficiency in the food field and reduce the exorbitant import bill in hard currency. This is part of the state's assurance of the rational use and conservation of natural resources for future generations.Sometimes, under compelling circumstances, there is a need to build buildings above agricultural estates for the existence of a worthy interest in care, which made the legislator attaches great importance to this issue and regulates it in all its aspects from the legislative point of view, and in terms of control on the ground.